2010
DOI: 10.1182/blood-2010-03-276998
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation of AML1-ETO–induced expansion of hematopoietic precursors in a Drosophila model

Abstract: Among mutations in human Runx1/AML1 transcription factors, the t(8;21)(q22;q22) genomic translocation that creates an AML1-ETO fusion protein is implicated in etiology of the acute myeloid leukemia. To identify genes and components associated with this oncogene we used Drosophila as a genetic model. Expression of AML1-ETO caused an expansion of hematopoietic precursors in Drosophila, which expressed high levels of reactive oxygen species (ROS). Mutations in functional domains of the fusion protein suppress the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
52
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 55 publications
2
52
0
1
Order By: Relevance
“…In mammals, RUNX1 acts mostly as a brake on blood cell progenitor proliferation, and decreased RUNX1 dosage, as well as MDS/AML-associated mutations or translocations affecting RUNX1, tend to promote aberrant self-renewal (34). Interestingly, RUNX1-ETO also promotes hematopoietic progenitor cell expansion in Drosophila (14,35), and both WT1 overexpression and activation of the Notch signaling pathway have been linked to RUNX1-ETO-induced AML (36,37). Given these similarities, characterizing the function of LZ in the control of crystal cell number may have broader implications.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, RUNX1 acts mostly as a brake on blood cell progenitor proliferation, and decreased RUNX1 dosage, as well as MDS/AML-associated mutations or translocations affecting RUNX1, tend to promote aberrant self-renewal (34). Interestingly, RUNX1-ETO also promotes hematopoietic progenitor cell expansion in Drosophila (14,35), and both WT1 overexpression and activation of the Notch signaling pathway have been linked to RUNX1-ETO-induced AML (36,37). Given these similarities, characterizing the function of LZ in the control of crystal cell number may have broader implications.…”
Section: Discussionmentioning
confidence: 99%
“…Munoz-Alonso et al, 2012;Palomero et al, 2006;Pierce et al, 2004;Zanet et al, 2005). Other targets include Hnf4, which was previously implicated in causing haemocyte expansion downstream of AML (Runx)-ETO (Sinenko et al, 2010), and several genes involved in cell motility (e.g. CLIP-120), as well as other conserved genes with unknown functions, such as CG32369 (LONRF1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Wg is also expressed in crystal cells, which strongly express hml. 36,68 In larvae expressing Idh-R195H in hemocytes, the pool of Wg1 hemocytes was expanded, and a majority of these Wg1 hemocytes weakly expressed hml ( Figure 5B), suggesting an expansion of prohemocytes.68 Nevertheless, a subpopulation of Wg1 cells strongly expressed hml, suggesting that crystal cells were also expanded. We confirmed that mature crystal cells were also increased in larvae expressing Idh-R195H using the crystal cell-specific C4 marker ( Figure 5C).…”
mentioning
confidence: 98%
“…[32][33][34][35] In fact, introduction of oncogenes such as AML1-ETO fusion and the hyperactive fly homolog of JAK2 can also block differentiation or stimulate proliferation of Drosophila blood cells. [36][37][38][39][40][41] We reasoned that Drosophila could provide insight into the function of IDH mutations from human cancer and could be used as a model to reveal genetic interactions that mutant IDH and D-2HG depend on to drive their biological phenotypes.Drosophila contains a single NADP 1 -dependent IDH called Idh (CG7176; note the lower-case "dh" for fly Idh, in contrast to all capital letters for human IDH1 and IDH2). Idh is 73% and 66% identical at the protein level to human IDH1 and IDH2, respectively (see supplemental Figure 1 on the Blood Web site).…”
mentioning
confidence: 99%
See 1 more Smart Citation